New drug-like small molecule antagonizes phosphatidylinositol (3,4,5)-trisphosphate (PIP3) in patients with conotruncal heart defects - Alaaeldin G. Fayez, PhD; Nora N. Esmaiel, PhD; Engy A. Ashaat, MD; Miral M. Refeat, PhD; Randa S. Lotfy, PhD; Haiam Abdel Raouf, PhD; Mona O. El Ruby, MD (Journal of Taibah University Medical Sciences, 2023)
الملخص: أهداف البحث: عيوب القلب الوعائية وراثية بشكل كبير وحوالي ثلث عيوب القلب الخلقية ناتجة عن عيوب القلب الوعائية. باستخدام التحليل اللاحق لعيوب القلب المخروطية -بيانات دراسة الترابط الجينومي الكامل ذات الصلة، تم افتراض مسار جديد مفترض لنقل الإشارات، يسمى ''فارس2-بك3كا-أ ك ت''، المرتبط بعيوب القلب الوعائية. كنا نهدف بشكل أساسي إلى التحقق من مسار ''فارس2-بك3كا-أ ك ت” بشكل تجريبي باستخدام المقياسين ''فارس2” و ''بيب3” في كل من مرضى عيوب القلب والعينة الضابطة، وإنشاء مثبط ''بيب3''، كواحد من مسببات عيوب القلب الضارة ذات الصلة، باستخدام استراتيجية تصميم الأدوية القائمة على ''أ ك ت''. طرق البحث: تم إجراء التنميط الجيني ''ار اس 2517582” والتعبير النسبي لـ ''فارس2” في 207 أفراد باستخدام تفاعل البلمرة المتسلسل الكمي، إلى جانب ذلك تم أيضا قياس ''بيب3” المحررة فى البلازما لدى 190 فردا باستخدام تقنية المقايسة الامتصاصية المناعية للإنزيم المرتبط. استخدمنا نموذج ميزات ''أ ك ت''-حامل الخاصة الدوائية لاكتشاف خصم ''بيب3” باستخدام أدوات حسابية متعددة وأدوات تقدير شبيهة بالعقاقير. النتائج: تم تأكيد إمراض عيوب القلب الوعائية بسبب فرط التحفيز المفرط لـ ''فارس2-بك3كا-أ ك ت” عن طريق ''فارس2” المرتفع و ''بيب3” في مرضى عيوب القلب الوعائية. حددنا جزيئا صغيرا جديدا، يسمى ''بيسب322''، قادرا على أن يقاوم ارتباط ''بيب3''، وتم منحه الأولوية من خلال الفحص الافتراضي لـ 21 جزيئا صغيرا افتراضيا. أظهر ''بيسب322” الحد الأدنى من التغير النسبى لاختلاف موقع جزيئاته ''رمسد''، وتقارب ربط عال، وثابت تفكك أقل من مجمع بيب3-أ ك ت” بمقدار 1.99 كيلو كالوري/مول مما يؤدي إلى تحول التوازن التفضيلى نحو تكوين معقد ''بيسب322-أ ك ت''. عرضت ''بيسب322” الخصائص الدوائية المقبولة وخصائص تشابه الأدوية وفقا لقاعدة ليبنيسكي و قاعدة امتصاص وتوزيع وتمثيل الغذاء وإفرازه المكونة من خمسة مصنفات. هذا هو أول جزيء محتمل كشبيه علاجى الدواء لمرضى عيوب القلب الوعائية الذين يعانون من ارتفاع ''بيب3''. الاستنتاجات: ''بيب3” هي مؤشرات حيوية تشخيصية مفيدة لمرضى عيوب القلب. يعد نموذج ميزات ''أ ك ت''-حامل الخاصة الدوائية نهجا ممكنا لاكتشاف المزيد من مضادات تأثير''بيب3''. يوصى بإجراء المزيد من اختبارات التطوير لجزئ ''بيسب322''. Abstract: Objectives: Conotruncal heart defects (CTDs) are highly heritable, and approximately one-third of all congenital heart defects are due to CTDs. Through post-analysis of GWAS data relevant to CTDs, a new putative signal transduction pathway, called Vars2-Pic3ca-Akt, associated with CTD has been hypothesized. Here, we aimed to validate the Vars2-Pic3ca-Akt pathway experimentally by measuring Vars2 and PIP3 in patients with CTDs and controls, and to construct a PIP3 inhibitor, as one of harmful-relevant CTD pathogenesis, through an Akt-based drug design strategy. Methods: rs2517582 genotype and relative Vars2 expression in 207 individuals were determined by DNA sequencing and qPCR respectively, and free plasma PIP3 in 190 individuals was quantified through ELISA. An Akt-pharmacophore feature model was used to discover PIP3 antagonists with multiple computational and drug-like estimation tools. Results: CTD pathogenesis due to Vars2-Pic3ca-Akt overstimulation was confirmed by elevated Vars2 and PIP3 in patients with CTDs. We identified a new small molecule, 322PESB, that antagonizes PIP3 binding. This molecule was prioritized via virtual screening of 21 hypothetical small molecules and it showed minimal RMSD change, high binding affinity andlower dissociation constant than PIP3-Akt complex by 1.99 Kcal/Mol, thus resulting in an equilibrium shift toward 322PESB-Akt complex formation. Moreover, 322PESB exhibited acceptable pharmacokinetics and drug likeness features according to ADME and Lipinski's rule of five classifiers. This compound is the first potential drug-like molecule reported for patients with CTDs with elevated PIP3. Conclusion: PIP3 is a useful diagnostic biomarker for patients with CTDs. The Akt-pharmacophore feature model is a feasible approach for discovery of PIP3 signalling antagonists. Further 322PESB development and testing are recommended.